THE PATTERN OF WHEEL SPOKE INJURY TREATED AT COMBINED MILITARY HOSPITAL RAWALPINDI - QADEER , A; MASOOD, T; AHMAD , S; JAMSHED, I; NAYEED, KU; ALAM, K (Biological and Clinical Sciences Research Journal, 2023)
This research investigated the characteristics and patterns of wheel spoke injuries treated at Combined Military Hospital Rawalpindi. The study was conducted at Combined Military Hospital Rawalpindi, a prominent healthcare facility in Rawalpindi, Pakistan, providing medical services to military personnel and civilians. The research analyzed data gathered over a year regarding wheel spoke injuries. A random sample of eighty-two patients was selected, and data was collected on demographic information, injury specifics, clinical presentations, treatments, and outcome measures to provide a quantitative analysis. The study's results showed that the average time elapsed from injury to presentation was 6 hours. Most injuries occurred on the right foot (37 patients) and were associated with the rear wheel (34 patients). Injuries to the lateral aspect of the ankle were common (73%), with the posterior ankle being the most frequent site (n=30). Soft-tissue injuries were classified into grades 0, 1, 2, and 3, with changes in grading noted in some cases. Patients with grade 0 or 1 injuries healed faster (mean 28 days) than those with grade 2 or 3 (mean 40 days). Eight patients had associated fractures, all healed without complications with a mean healing time of 18 days. The study concluded that wheel spoke injuries are common and are often found near the Achilles tendon. Injury classification is critical for treatment decisions and predicting prognosis. Monitoring for infection and necrosis within 48 hours is vital due to poor vascularity. Customized treatment approaches, including below-knee back splints, ankle foot orthoses, and debridement, are recommended based on injury characteristics.